Leonardo's Choice Genetic Technologies and Animals - Gigliotti, Carol (Springer Netherlands : Imprint: Springer, 2009)
Leonardo's Choice: Genetic Technologies and Animals is an edited collection of twelve essays and one dialogue focusing on the profound affect the use of animals in biotechnology is having on both humans and other species. Communicating crucial understandings of the integrated nature of the human and non-human world, these essays, unlike the majority of discussions of biotechnology, take seriously the impact of these technologies on animals themselves. This collection's central questions revolve around the disassociation Western ideas of creative freedom have from the impacts those ideas and practices have on the non-human world. This transdisciplinary collection includes perspectives from the disciplines of philosophy, cultural theory, art and literary theory, history and theory of science, environmental studies, law, landscape architecture, history, and geography. Included authors span three continents and four countries. Included essays contribute significantly to a growing scholarship surrounding "the question of the animal" emanating from philosophical, cultural and activist discourses. Its authors' are at the forefront of the growing number of theorists and practioners across the disciplines concerned with the impact of new technologies on the more-than-human world. Both a wide-ranging discussion of animals and biotechnology in science and culture, and a bracing call to action regarding animal exploitation, Leonardo's Choice intervenes thoughtfully, yet forcefully, in one of the most pressing issues of our time.-Cary Wolfe, Author of Animal Rites (Chicago, 2003) ...when artists are entering the lab, and scientists are collaborating in bio-art, this book satisfies the need to interrogate the meanings of such boundary challenges - around both the dangers of capture and complicity, and the promises of critical scientific endeavour.-Dr. Richard Twine, ESRC Centre for Economic and Social Aspects of Genomics, Lancaster University, UK.    .